Dinamika Majelis Ulama Indonesia Pada Masa Orde Baru:Kepemimpinan Hamka, Syukri Ghozali, dan Hasan Basri dalam Negosiasi Otoritas Keagamaan dan Politik Negara - Wildan Insan Fauzi; Yeni Kurniawati; Iing Yulianti (Tarikh : Journal of Islamic History and Civilization, 2026)
This article analyzes the dynamics of the Indonesian Ulema Council (MUI) during the New Order era, focusing on three leadership phases: Hamka, Syukri Ghozali, and Hasan Basri. This article seeks to develop new ideas by incorporating more recent open-ended studies on Hamka, fatwas, religious authority, and Islam-state relations in Indonesia. The method employed is a literature-based historical approach, involving heuristics, source criticism, interpretation, and historiography. The primary sources for this article consist of MUI archives, MUI fatwas, the evolution of religious authority, and contemporary studies on Hamka’s thought. The findings indicate that the MUI cannot be understood solely as an extension of the state or as a fully independent religious opposition. During Hamka’s era, the MUI appeared relatively more assertive in upholding moral autonomy, particularly in the Christmas fatwa controversy. During Syukri Ghozali’s tenure, the MUI tended to emphasize the function of safeguarding orthodoxy through its handling of movements deemed deviant. During Hasan Basri’s tenure, the MUI developed a strategy of critical accommodation—being more cautious toward the state while still asserting leverage on issues such as the single-party principle, SDSB, inheritance law, and the Darul Arqam movement. The shift in the MUI’s leadership style is best understood as an institutional adaptation to the New Order’s power structure, changes in the socio-religious landscape, and the transformation of Islamic authority in Indonesia. Thus, the MUI serves as a forum for negotiation that brings together the aspirations of the Muslim community, the interests of the state, and the authority of the ulama in an ever-evolving form.